Cigarette smoke alters the proteomic profile of lung fibroblasts. Issue 6 (19th June 2015) - D'Anna, Claudia; Cigna, Diego; Costanzo, Giorgia; Bruno, Andreina; Ferraro, Maria; Di Vincenzo, Serena; Bianchi, Laura; Bini, Luca; Gjomarkaj, Mark; Pace, Elisabetta
<x xml:space="preserve">Abstract</x> The protein identified here may offer a new insight into deciphering damage caused by cigarette smoke.